E-TRAINING APPLICATION FOR JOB VACANCIES BASED ON COMPUTER BASE TEST - Wahyu Tri Yanto; Ahmad Zakir; Arie Rafika Dewi (Cattleya Darmaya Fortuna, 2026)
In today's digital age, the technology industry continues to grow at a rapid pace, and the use of mobile devices is increasingly widespread. The internet is one of the results of the development of computer technology, at this time almost everyone uses the internet for the latest information. Many various job vacancy search places on the internet such as jobstreet.co.id, loker.id, glints.com and others, of the many sites or applications where job vacancies mostly only display job vacancy features. causing prospective applicants to face difficulties in finding job vacancies that match their expertise. And companies or recruiters often face difficulties in evaluating the expertise of potential applicants. Based on these problems, the author adds skills and experience development facilities by adding training features that provide relevant and quality learning materials, and with the test feature before sending job application documents, this can increase the efficiency of companies or recruiters in the selection process of prospective job applicants. In addition, test results can also help applicants improve their skills with useful feedback to add experience, with this research applicants have the potential to obtain career opportunities that match their expertise.